Perjanjian Pengikatan Jual Beli Hak Atas TanahBerdasarkan Akta Notaris - Mochamad Amin; Teguh Anindito; Wiwin Mochtar Wiyono (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2019)
The purpose of this study was to determine the strength of the sale and purchase agreement deed of land rightsmade by a Notary in the implementation of the deed of sale and purchase of land. To achieve these objectivesthe author uses a normative juridical approach, Research Specifications are legal in nature. The method ofpresenting date is presented in the form of descriptions which are grouped and then arranged systematically.Conclusion: based on the results of the research and discussion shows that the legal strenght of the sale andpurchase rights agreement on land rights made by a Notary in the implementation of the Sale Deed is verystrong, because the deed is anotary deed which is an authentic deed, authorization that cannot beingwithdrawn in the sale and purchase agreement is not included in the absolute power that is prohibited by theMinister of Home Affairs’ Instruction No. 14 of 1982 concerning Prohibition of the Use of Absolute Authoritiesas the Transfer of Right to Land, so that legal status is valid.